1992
DOI: 10.1111/j.1600-0749.1992.tb00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Biosynthesis From Dopamine. II. A Mass Spectrometric and Collisional Spectroscopic Investigation

Abstract: Electron impact (EI) and fast atom bombardment (FAB) mass spectrometry together with collisional activation (CA) experiments were applied to the study of the oxidation pathway of dopamine by tyrosinase. In order to prevent attachment of the protein to the highly reactive intermediates, ultrafiltration was employed to remove the enzyme at different reaction times. FAB, privileging molecular species formation, was successfully used for identification of transient intermediates and their relative concentrations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Recent studies have revealed that GSTM1 and GSTM2 in the -class GST's can catalyze the conjugation reaction between GSH and catecholamine o-quinones under physiological conditions (13,14). These findings are interesting within the context of the hypothesis that nurodegeneration due to oxidative metabolytes in the central nerve system may contribute to the development of schizophrenia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies have revealed that GSTM1 and GSTM2 in the -class GST's can catalyze the conjugation reaction between GSH and catecholamine o-quinones under physiological conditions (13,14). These findings are interesting within the context of the hypothesis that nurodegeneration due to oxidative metabolytes in the central nerve system may contribute to the development of schizophrenia.…”
Section: Discussionmentioning
confidence: 96%
“…Since the human GSTM1 and GSTM2 have been detected in the brain (13,14), this defect in the detoxification mechanisms due to reduced or negative activities of these enzymes may result in an excess of chatecholamine o-quinones within the brain. If such a phenomenon were to take place in the dopaminergic-, noradrenergic-, and adrenergic-nerve systems in the brain, certain forms of schizophrenia or other neurological disorders could follow.…”
mentioning
confidence: 99%
“…X-ray diffraction studies 21,22 and scanning tunneling microscopy measurements [23][24][25] showed that the size of eumelanin protomolecules is around 15-20 Å, which suggested that the tetramers and pentamers formed by covalently bonded DHIs are the most possible molecular structures of eumelanin. Matrix-assisted laser desorption/ionization mass spectrometry studies [26][27][28][29][30][31] showed that the mass of eumelanin protomolecules is within or below B600-1,200 amu, and large polymeric structures are not observed, with the exception of the data reported in a recent report 32 . Hence, most of the investigations performed by mass spectrometry supported that the tetramers and pentamers constitute the majority of eumelanin, while slightly larger structures, such as the hexamers and octamers, are also possible.…”
mentioning
confidence: 91%
“…The production of melanogenesis intermediates from dopamine using tyrosinase as enzyme has also been confirmed by means of collisional spectroscopy. 19 The present investigation was based on the reactions of dopamine with peroxidase and Dopa with both tyrosinase and peroxidase. The study was performed by drawing samples at various reaction times and analysing them (after ultrafiltration to remove the enzyme) by matrixassisted laser desorption/ionization (MALDI) mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%